Decentralisatie van klassieke en hedendaagse films : kataloog 1979-80. (Brussel : Ravensteingalerij 72, 1979)
Bergman, Ingmar ; Carné, Marcel ; Cavalcanti, Alberto ; Costard, Hellmuth ; Dekeukeleire, Charles ; Delvaux, André ; De Sica, Vittorio ; Dreyer, Carl Theodor ; Dudow, Slatan ; Eisenstein, Sergei Mikhailovitch ; Fellini, Federico ; Godard, Jean-Luc ; Herzog, Werner ; Kramer, Robert ; Kuijpers, Rik ; Lang, Fritz ; Malraux, André ; Michiels, Ivo ; Murnau, Friedrich Wilhelm ; Ophuls, Max ; Ozu, Yasujiro ; Pabst, Georg Wilhelm ; Renoir, Jean ; Resnais, Alain ; Sandrich, Mark ; Schmid, Daniel ; Stevens, George ; Storck, Henri ; Varda, Agnès ; Védrès, Nicole ; Verhavert, Roland ; Vertov, Dziga ; Vidor, King ; Visconti, Luchino ; Wiene, Robert
boek